2019
DOI: 10.32628/cseit1952277
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Prediction using SVM with PCA Feature Selection Method

Abstract: Cancer has been characterized as one of the leading diseases that cause death in humans. Breast cancer, being a subtype of cancer, causes death in one out of every eight women worldwide. The solution to counter this is by conducting early and accurate diagnosis for faster treatment. To achieve such accuracy in a short span of time proves difficult with existing techniques. Also, the medical tests conducted in hospitals for detecting cancer is expensive and is difficult for any common man to afford. To counter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…The results for Yang and Xu (2019) and Yin et al (2016) are also slightly better than our results, because they do not use cross-validation and simply group some datasets into testsets, potentially making test dataset easier to distinguish. Yadav et al (2019) also used SVM classifier whose result is different from ours, it is also because of the partition of test dateset, they used 40% data as test dataset. We used 10-fold cross-validation, and the results are less random and more reliable.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…The results for Yang and Xu (2019) and Yin et al (2016) are also slightly better than our results, because they do not use cross-validation and simply group some datasets into testsets, potentially making test dataset easier to distinguish. Yadav et al (2019) also used SVM classifier whose result is different from ours, it is also because of the partition of test dateset, they used 40% data as test dataset. We used 10-fold cross-validation, and the results are less random and more reliable.…”
Section: Methodsmentioning
confidence: 85%
“…With the comparison of the results between previous studies (Fan et al, 2011; Krishnan et al, 2010; Mert et al, 2014; Sweilam et al, 2010; Yadav et al, 2019; Yang et al, 2019) and this study in Table 7, it can be found that the 10-CV, PCA-SVM (RBF) used in this study has the highest accuracy (97.19%) except the best result (98.90%) of CBFDT, which was proposed by Fan et al (2011). They used all the attributes, while the results obtained in this paper is based on PCA-SVM using six principal components only.…”
Section: Methodsmentioning
confidence: 86%
“…(Yadav & Sohani, 2019) [7] , utilized the MM1 queue model to estimate the performance of the food chain's services, and described how as the number of servers grows, so does the system's service quality. The "Queuing model as a Method of Queue resolution in Nigeria Banking Sector" is the subject of research by Anichebe (2019) [8] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Esto perjudica a los clientes y frena la expansión de las empresas. Una empresa debe trabajar siempre para mejorar sus servicios, concentrarse en satisfacer las necesidades de los consumidores de la manera más eficaz posible y emplear una estrategia que funcione para la empresa si quiere tener éxito en el despiadado mercado actual (Yadav & Sohani, 2019).…”
Section: Antecedentes De Sistemas De Colasunclassified